Bridging Gaps in Mental Health Care Through Music Therapy: A Narrative Review - Nazaruddin, M. Arief; Mahfudzi, Aan (Harmonia : Journal of Music and Arts, 2025)
Music therapy has gained increasing recognition as a non-pharmacological intervention for improving mental health in both clinical and community settings. This narrative review aimed to synthesize current evidence on its effectiveness, methodological approaches, and systemic challenges. Literature was systematically identified through major databases including PubMed, Scopus, and Google Scholar, using keywords such as "music therapy," "mental health," "anxiety," "depression," and "stress." Inclusion criteria focused on empirical studies, randomized controlled trials, cohort research, and systematic reviews addressing mental health outcomes. Findings demonstrate that music therapy significantly reduces symptoms of anxiety, depression, and stress while enhancing social interaction and overall well-being. Clinical studies reported improvements among intensive care patients and older adults, while community-based interventions benefitted adolescents and caregivers. Technological innovations, including mobile applications and digital delivery platforms, have expanded accessibility and demonstrated outcomes comparable to conventional therapy. Global evidence suggests consistent benefits across cultural and healthcare contexts, reinforcing music’s universality as a therapeutic medium. However, systemic barriers such as limited policy support, inadequate professional training, and stigma against non-pharmacological interventions hinder widespread adoption. The review concludes that music therapy offers substantial promise for integration into mental health care but requires stronger evidence from long-term studies and culturally diverse populations. Policy reform, standardized methodologies, and digital innovation are key strategies to ensure sustainable implementation. By addressing current gaps, music therapy can be established as an essential component of comprehensive mental health care.